OBESITY AND METABOLIC SYNDROME IN CHILDREN AND YOUTH: A HEALTH RISK WE CANNOT AFFORD - Serge P. von Duvillard (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2012)
Ample observational and empirical evidence has been provided that indicates that childhood metabolic syndrome risk factors inevitably lead to significantly more profound health risk factors of developing potent adulthood metabolic syndrome.  Much of these data has been provided from medical, nutritional, health, pediatric, physical education and associated communities. Perhaps the most visible and observable health risk factor among children (here referred to as youth) is the childhood obesity. Childhood obesity has reached epidemic proportions in western industrialized countries and is also becoming significantly more prevalent in Slovenia. The youth inactivity is attributed directly to epidemic and perhaps exponential occurrence of obesity in pediatric and youth populations.  The symptoms and signs of metabolic syndrome have previously been attributed mostly to the adult population; however, similar observations have been identified and observed in young and very young segment of population. The typical risk factors of metabolic syndrome in youth, in adolescents, and in adulthood have been commonly identified to be: stress, overweight and obesity, sedentary life cycle, aging, diabetes mellitus, coronary heart disease, lipodystrophy and several others. This presentation will review and address several well known risk factors of developing metabolic syndrome in young years that directly contributes to adult obesity and are exhibited in significantly higher rates of hypertension, dyslipidemias, and insulin resistance, which are all risk factors for coronary heart disease, the leading cause of death in North America and may also apply to Slovenia.  Many of these risk factors are modifiable (nutrition, smoking, sedentary life style, vigorous physical activity, reduction in TV and computer game times, etc.) with specific emphasis on very young, young, adolescents and profound consequences for adulthood.  Several recommendations will be proposed that may contribute to reduction of health risk factors among youth.  The references have been generated from scientific literature and available information from various data bases in the United States, Center for Disease Control, National Institutes of Health, World Health Organization and several other relevant sources. These data and facts are very relevant to Slovenia because the inevitable truth is that these risk factors are "creeping up" into Slovenian society and it is my hope that you will be proactive and address these issues and act proactively rather than just stand by and observe the decline of health, especially among youth that will result in very costly financial burden of Slovenia for many years and decades to come.